The Human Body and Integrative Bioethics: The Meaning of the Body as a Symbolic Construct - Trako, Tijana (2010)
The human body was understood differently through history of modern post-industrial society, as well as other societies and cultures. Also, the ways in which we understand and approach the human body differ across various scientific disciplines: medicine, sociology, theology, philosophy, psychology, etc. The body is ascribed different meanings with regards to different contexts, as well as the subjects who ascribe the meanings. This is important to take into consideration, especially when examining issues regarding the relation towards life within bioethical perspective – abortion, euthanasia, death penalty, disability, etc. The paper therefore places particular emphasis on the human body as the key component of the nature/human dichotomy integral to bioethical considerations. The body is observed through three main categories in contemporary scientific theory: a) the body as object (law, medicine, theology ; regulated, institutionalized power over the body ; e.g. Foucault, Descartes) ; b) the body as abject (psychology, belief systems ; spiritual, psychological power over the body ; Douglas) ; and c) the body as subject (integrative disciplines, connection between the body and the mind ; body as self-constructed, self-regulated) ; (Gregan, 2006). The main thesis of the paper is that, only with the understanding of the ways in which different groups approach the body, the meanings they attribute to it, and how they (mis)use it, we can better understand different attitudes in bioethical discussions, and truly develop bioethics as an integrative discipline. Furthermore, the symbolism of the body can be widened to include the symbolism of animal bodies, as well as plants (Visković, 1996 ; 2001 ; 2009). Symbolism, inherent only to humans, is crucial in the understanding of selves and our natural environment, because a group makes its decisions on generally accepted meanings. Only with the understanding of the symbolism of the body, as the basis of the relation of different disciplines towards the issues of life, we can go into deeper discussions regarding contemporary bioethical issues.
Projekt MZOS
ENG